Colonizing Microbes, IL-10 and IL-22: Keeping the Peace at the Mucosal Surface - Kidess, Evelien; Kleerebezem, Michiel; Brugman, Sylvia (Frontiers in Microbiology, 2021)
Our world is filled with microbes. Each multicellular organism has developed ways to interact with this microbial environment. Microbes do not always pose a threat; they can contribute to many processes that benefit the host. Upon colonization both host and microbes adapt resulting in dynamic ecosystems in different host niches. Regulatory processes develop within the host to prevent overt inflammation to beneficial microbes, yet keeping the possibility to respond when pathogens attempt to adhere and invade tissues. This review will focus on microbial colonization and the early (innate) host immune response, with special emphasis on the microbiota-modifying roles of IL-10 and IL-22 in the intestine. IL-10 knock out mice show an altered microbial composition, and spontaneously develop enterocolitis over time. IL-22 knock out mice, although not developing enterocolitis spontaneously, also have an altered microbial composition and increase of epithelial-adherent bacteria, mainly caused by a decrease in mucin and anti-microbial peptide production. Recently interesting links have been found between the IL-10 and IL-22 pathways. While IL-22 can function as a regulatory cytokine at the mucosal surface, it also has inflammatory roles depending on the context. For example, lack of IL-22 in the IL-10-/- mice model prevents spontaneous colitis development. Additionally, the reduced microbial diversity observed in IL-10-/- mice was also reversed in IL-10/IL-22 double mutant mice (Gunasekera et al., 2020). Since in early life, host immunity develops in parallel with colonizing microbes, there is a need for future studies that focus on the effect of the timing of colonization in relation to the developmental phase of the host. To illustrate this, examples from zebrafish research will be compared with studies performed in mammals. Since zebrafish develop from eggs and are directly exposed to the outside microbial world, timing of the development of host immunity and subsequent control of microbial composition, is different from mammals that develop in utero and only get exposed after birth. Likewise, colonization studies using adult germfree mice might yield different results from those using neonatal germfree mice. Lastly, special emphasis will be given to the need for host genotype and environmental (co-housing) control of experiments.